The Effectiveness Of Using A Frequency Generator Application In Enhancing Students' Conceptual Understanding Of Determining The Speed Of Sound - Sayyadi, Muhammad; Ahsan, Moh; Jufriadi, Akhmad (Program Studi Pendidikan IPA FKIP Universitas Jember, 2025)
This research utilizes a frequency generator application on smartphones with the aim of enhancing students' understanding of the concept of sound resonance in closed organ pipes. The study employs a pretest-posttest design with a control group that was not selected randomly. The method used is non-probabilistic sampling (convenience sampling). The sample used in this study consists of fourth-semester Elementary Teacher Education (PGSD )students who are taking the science learning course. Data collection was conducted using a Concept Understanding Instrument Sheet. The percentage of students' concept understanding above the average increased from 40.1% to 63.4%. This indicates that the concept understanding attained improved after receiving treatment in the form of the frequency generator application. The N-Gain test results yielded an average score of 0.68.